PENGEMBANGAN SUMBER DAYA MANUSIA STRATEGIS DI MADRASAH LAILIYAH PESANTREN ROUDHLOTUS SIDQI WALED KABUPATEN CIREBON - Ummu Aiman; Dewi Cahyani; Moh. Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze strategic human resource (HR) development at the Lailiyah Islamic Boarding School of Roudhlotus Sidqi Waled in Cirebon Regency. The main focus of the study includes strategies for improving educator competency, strengthening the Islamic boarding school's work culture, and identifying challenges faced in the HR development process. The approach used is qualitative with a case study method, utilizing in-depth interviews, participant observation, and documentation analysis to gain a comprehensive understanding of HR development practices within the madrasah. The results show that HR development at this madrasah takes place through a combination of traditional Islamic boarding school approaches and modern management principles, emphasizing strengthening pedagogical competency, fostering Islamic values, and fostering collaboration and communication between teachers. In addition, a supportive work culture, participatory leadership, and emotional closeness between institutional components are key factors in creating a conducive learning environment. However, several challenges remain, including limited access to external training, suboptimal use of learning technology, and high teacher workloads that can impact the effectiveness of HR development. This study confirms that human resource development in Islamic boarding schools (madrasah) is a continuous process that relies not only on formal training but also requires strengthening values, organizational culture, and harmonious social interactions within the Islamic boarding school environment. These findings provide important implications for the management of Islamic boarding school education, particularly in designing human resource development strategies that are holistic, sustainable, and relevant to the challenges of the times. Keywords: Human Resource Development, Madrasah Lailiyah, Islamic Boarding School, Educational Management, Teacher Competence.